2012
DOI: 10.1177/1532440011433590
|View full text |Cite
|
Sign up to set email alerts
|

Building an Integrated Model of Trial Court Decision Making: Predicting Plaintiff Success and Awards across Circuits

Abstract: This study creates and empirically tests an integrated model of trial court decision making to explore the hypothesis that jury verdicts reflect the social, political, and economic attributes of the community in which the court resides. In addition, the analyses examine the influence of attorneys, litigants, case facts, and judges on trial outcomes. Using an original data set comprising all reported civil trial verdicts decided in the state of Alabama from 2002 to 2008, we uncover strong evidence that communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Many trial court scholars hold firmly to the belief that trial judges are primarily administrators, appliers of law, and organizational bureaucrats, spending their time in rote activities like holding hearings and supervising jury trials. Scholars often fail to find evidence that trial judges’ identities—including things like their ideological preferences—affect outcomes (e.g., Dumas and Haynie 2012; Keele et al 2009). If this view of trial judging is correct and generalizable, when applied to diversity judging, it could very well mean that even if diverse trial judges wish to favor diverse plaintiffs, their hands are often tied.…”
Section: How Diversity May Affect Trial Judgingmentioning
confidence: 99%
“…Many trial court scholars hold firmly to the belief that trial judges are primarily administrators, appliers of law, and organizational bureaucrats, spending their time in rote activities like holding hearings and supervising jury trials. Scholars often fail to find evidence that trial judges’ identities—including things like their ideological preferences—affect outcomes (e.g., Dumas and Haynie 2012; Keele et al 2009). If this view of trial judging is correct and generalizable, when applied to diversity judging, it could very well mean that even if diverse trial judges wish to favor diverse plaintiffs, their hands are often tied.…”
Section: How Diversity May Affect Trial Judgingmentioning
confidence: 99%
“…Prior research in criminal sentencing and employment discrimination research has identified three factors of social context that may be particularly likely to shape decisions in employment discrimination cases: local political orientation (Garnett, 2012; McVeigh & Sobolewski, 2007; Skaggs, 2008, 2009; Songer & Unah, 2006), rurality (Dumas & Haynie, 2012; Eason et al, 2017; Oliver & Mendelberg, 2000; Songer & Unah, 2006), and presence in the south (Glaser, 1994; Oliver & Mendelberg, 2000; Songer & Davis, 1990). All three are relevant to shaping local norms related to discrimination, race, and gender.…”
Section: Discrimination Court Communities and Judicial Identitiesmentioning
confidence: 99%
“…A 2013 Pew study shows that rural, suburban, and urban residents have vastly different opinions on whether Black Americans are treated fairly at work, by the police, by the courts, in elections, at schools, in businesses, and by the healthcare industry (Pew Research Center, 2013). Previous research looking at all cases in Alabama found variations in civil cases proceeded, based on whether they occurred in a rural or urban county (Dumas & Haynie, 2012). Despite evidence that rural residents tend to have different racial opinions than White Americans, no research has examined if this influences decisions in employment discrimination cases.…”
Section: Discrimination Court Communities and Judicial Identitiesmentioning
confidence: 99%
“…Within those broad categories, variation remains in success before the courts. Largely, poor individuals or minorities are ranked as the least advantaged, and the federal government is ranked as the most advantaged, with other actors like individuals, corporations, and state governments ranking somewhere in between (Sheehan, Mishler and Songer 1992;Songer and Haire 1992;Dunworth and Rogers 1996;Songer, Sheehan and Haire 1999;Dumas and Haynie 2012;Boyd 2015). 3 As a result, we might expect that private companies will be relatively advantaged in litigation when they are facing one-shot litigants like prisoners.…”
Section: Prison Privatization and Judicial Decision-makingmentioning
confidence: 99%